Effect of Extraction Methods on Fatty Acid Composition, and Chemical and Physical Characteristics of Oil from House Crickets (Acheta domesticus) - Ngampeerapong, Chitraporn; Nakprasom, Kanjana; Wangcharoen, Wiwat; Rahong, Nunnapat; Changpradit, Tada; Waseeanuruk, Thvunrud; Tangsuphoom, Nattapol (Journal of Food Technology, Siam University, 2024)
House crickets (Acheta domesticus (L.)) are recognized as a high-quality protein source with fat being the second abundant component. Cricket oil is the by-product of cricket protein production, in which dried cricket powder is defatted prior to protein extraction. This study assessed the quality of oils extracted from house crickets using different methods, namely solvent extraction by hexane and screw pressing. Fatty acid composition and physicochemical properties of the obtained oils were compared. It was found that solvent extraction gave 1.6 times higher oil yield than screw pressing. The fatty acid composition of both oils was similar, of which linoleic acid, oleic acid and palmitic acid were the three most abundant fatty acids. Cricket oils were clear yellow with similar refractive indices (1.465-1.466). However, the oil from screw pressing was lighter in color (L*=19.63 vs. 13.92) than that extracted using hexane but exhibited less yellowness (b*=18.76 vs. 26.54). The screw-pressed oil also had a lower peroxide value (7.93±0.02 vs. 25.12±2.24 meqO2/kg) and acid value (4.95±0.03 vs. 5.83±0.19 mg KOH/g), but higher water activity than its counterpart (0.357±0.004 vs. 0.245±0.002). In conclusion, solvent extraction and screw pressing had similar effect on cricket oil quality. The chemical and physical characteristics of the cricket oils suggest their potential as edible oils for use in food products.